(3bUjOI aj CdMGf GdShGLYs - (3GdCfOdSj, LGHQ Hf SYjOs
(3ChdgG (B:s
(3hUdJ adjgffj djd GdhUGd (B*** (3hUdgG GdZGdj HfaS ZjQ ZGdj , bd def HTQfj deG CJJ (B*** (3gPg QhMj aj GdHTQ Ch eGdjs
(3BNQgG (B:s
(3OGe ddCbdGe RjfG ajg (B*** (3cSjJ Mdi GdeYGfj hGdeYGdjs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdCOHs